Investigation in to the causes of severe roof problems in some Indian coal mines and formulation of guidelines to reduce ground control problems. (20th February 2012) - Sengupta, S.; Sinha, R.K.; Subrahmanyam, D.S.; Joseph, D.
Severe roof stability problems are encountered in many of the Indian Coal Mine the cause of which could not be understood properly and thus no preventive measure could be taken. The discontinuous and random roof failure in the same stretch of level galleries/dip rises under the same geological conditions defied any logic. Actual stress measurement in two mines having such problems revealed perturbed stress condition which backed by numerical modelling helped in understanding the cause and pattern of failure. Based on the study a broad guideline of support system to deal with the roof failure problem could be evaluated.